Enfermería en el control el dolor agudo mediante terapias alternativas - Flores Nazareno, Jocelyn Fernanda (2022)
ABSTRACT: Pain is a first-line health problem, being one of the most regular causes of consultation in the first-level care worldwide, which affects people, to a greater or lesser extent, their health, social, labor, and personal states. Alternative therapies are mainly important since they promote healing and comfort, they provide interventions complementary to pharmacological treatment. A documentary and descriptive study were elaborated to determine the alternative therapies most used by nurses in the control of acute pain through the compilation of information from several documents published on scientific bases: Scielo, Lilacs, Pubmed, Elsevier, Proquest, Hindawi, and Medway, Google Scholar, and university repositories; disseminated between 2017 and 2022, from which 65 articles were taken for the literature review; for the results of the research, first a triangulation was performed through the criteria of the different authors cited, regarding alternative therapies most used by nursing worldwide for the management of acute pain, update in terms of scientific substantiation including aspects of relevance such as level of efficacy and system in which it acts and description of the contributions of nursing throughout history in the area of alternative therapies, which represent aspects of relevance that we must adapt to professional life. The primary alternative therapies nurses use worldwide are acupuncture, reflexology, yoga, aromatherapy, and massage. Regarding nursing contributions to alternative therapies, Florence Nightingale, who introduced non-pharmacological interventions, mainly massage; Eunice Inghan, creator of the book "What the feet can tell us," including the first reflexology map; Martha Rogers, who promoted alternative, oriental and therapeutic therapies; Madeleine Leininger, who suggests knowing the cultural customs to provide holistic care: Marie-Françoise Collière, care provided through the hands using plants, oils and massages: Dolores Krieger and Dora Kunz, introduction therapeutic touch: Rosemarie Rizzo Parse, the human being is free to choose his orientations of how to be cared for: Rosette Poletti, provided holistic health practices, reflexology visualization, and relaxation and finally Barbara Dossey, pioneer of holistic nursing, creator of 16 books based on multicultural nursing. Keywords: alternative therapies, pain, nursing, holistic care